2018
DOI: 10.3390/f9070390
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tree Community Composition and Carbon Stock under Natural and Human Disturbances in Andean Forests, Peru

Abstract: Deforestation and forest degradation in Andean forests is influenced by natural and social environments including a wide elevation range and anthropogenic disturbance. Tree community composition is receiving attention as a key indicator of forest degradation. However, difference in factors affecting community composition at different elevation zones remains unclear. We aimed at elucidating factors (natural and human disturbances, and forest characteristics) that influence the variations in community compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The discretization of the plots according to the negative or positive nature of the β-diversity scores has been reported before, also relating biomass mean values to certain classes [10]. The previous study and other related [11,45] had found a clear link between community taxonomic diversity and carbon stock through patches with human disturbances. Our findings support that relation, because the greatest differences in biomass and beta diversity were found between the same areas.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The discretization of the plots according to the negative or positive nature of the β-diversity scores has been reported before, also relating biomass mean values to certain classes [10]. The previous study and other related [11,45] had found a clear link between community taxonomic diversity and carbon stock through patches with human disturbances. Our findings support that relation, because the greatest differences in biomass and beta diversity were found between the same areas.…”
Section: Discussionsupporting
confidence: 54%
“…Actually, even with the relatively lower correlation of the LiDAR metrics, the addition of the CHM variable to the model improved its predictive power, representing almost a third of the total explained variability. Height variables had been considered before as key measures for evaluating variations in community composition [11], and in this study, the canopy height was especially momentous for distinguishing the dissimilarity in tree species composition between the shorter areas with agriculture disturbance history, and the taller areas with selective logging disturbance history (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations